Heat transfer in porous media - Beck, J. V. (James Vere), 1930-; Yao, L. S.; American Society of Mechanical Engineers. Heat Transfer Division; Winter Annual Meeting of the American Society of Mechanical Engineers (1982 : Phoenix, Arizona) (New York : ASME, 1982)
40